Effect of injection brine composition on wettability and oil recovery in sandstone reservoirs. (15th October 2016) - Hua, Zhao; Li, Mingyuan; Ni, Xiaoxiao; Wang, Haoyi; Yang, Zihao; Lin, Meiqin
Highlights: Bridging action of Ca 2+ results in more oil-wet surface and limited oil recovery. Wettability alteration and oil layer instability are the mechanism to EOR by LSF. LSF effect was investigated by surface force model in a cylindrical pore. Abstract: Wettability alteration and enhanced oil recovery (EOR) of sandstone by low salinity waterflooding (LSF) have become the focus of many studies. However, there is no clear explanation of how the ion composition of brines influences the LSF effect. In this paper, imbibition, ζ-potential measurements, core displacement, and microscopic displacement experiments were adopted to investigate the effect of brine composition on the wettability and oil recovery of sandstone reservoirs and the Ca 2+ bridge action between rock surface and the acidic components in crude oil. Besides, the surface force model in a cylindrical pore was also developed for investigating the mechanisms behind wettability alteration and EOR by LSF. The results show that Ca 2+ in the brine acted like a bridge between the negatively charged sites on rock surface and dissociated acidic components in crude oil, and the acidic components in crude oil played an important role in the Ca 2+ bridge action. Divalent cations (e.g. Ca 2+ ) in the brine hindered the low salinity effect, and thus the low-salinity brine without divalent cations showed optimal low salinity effect. Lowering the salinity of 1:1 electrolyte solution (e.g., NaCl solution) caused the expansion of the electrical double layer and increasing disjoining pressure between rock/brine and oil/brine interfaces, and thus the rock surface changed to be more water-wet and a thicker wetting-water film could be stable between rock surface and crude oil. When injecting low salinity NaCl brine, more water-wet state improves the ability of water imbibition in small pore and a thicker wetting-water film promotes destabilization of oil layers adhering to sandstone surface, thus resulting in EOR.